Adhesive small bowel obstruction: Single band or matted adhesions? A predictive model based on computed tomography scan. Issue 6 (June 2021) - Guerrini, Jacopo; Zugna, Daniela; Poretti, Dario; Samà, Laura; Costa, Guido; Mei, Simona; Ceolin, Martina; Biloslavo, Alan; Zago, Mauro; Viganò, Luca; Kurihara, Hayato
Abstract : BACKGROUND: Preoperative identification of the cause of adhesive small bowel obstruction (ASBO) is crucial for decision making. Some computed tomography (CT) findings can be indicative of single adhesive bands or matted adhesions. Our aim was to build a predictive model based on CT data to discriminate ASBO due to single adhesive band or matted adhesions. METHODS: A retrospective single center study was conducted, covering all consecutive patients with a preoperative CT scan, undergoing urgent surgery for ASBO between January 1, 2005, and December 31, 2017. Preoperative CT scans were blindly reviewed, and all the CT findings indicative of single adhesive band or matted adhesions described in literature were recorded. According to intraoperative findings, ASBOs were retrospectively classified into single band and matted ASBO. All observed CT findings were compared between the two groups. A predictive model based on logistic regression was developed, and its ability was quantified by discrimination and calibration. Internal cross-validation was conducted by bootstrap resampling. RESULTS: A total of 116 patients were analyzed (males, 53.5%; median age, 68 years; single band ASBO in 65.5% of cases). The odds of single band ASBO were increased four times in presence of complete obstruction (odds ratios, 4.19; 95% confidence interval, 1.49–12.56) and seven times in presence of fat notch sign (odds ratios, 7.37; 95% confidence interval, 1.83–40.03). The predictive model combining all CT findings had an accuracy of 86% in single band ASBO prediction. Accuracy decreased to 79% in the internal validation. Sensitivity, specificity, and positive and negative predictive values were calculated at different cut-points of the predicted risk: using a 0.70 cut-point, the specificity is 80%, the sensitivity is 68%, and the positive and negative predictive values are 87% and 57%, respectively. CONCLUSION: The proposed predictive model based on combination of specific CT findings may elucidate whether ASBO is caused by single bands or matted adhesions and, consequently, influence the clinical pathway. LEVEL OF EVIDENCE: Prognostic study, level IV Abstract : Supplemental digital content is available in the text.